COMBINATION OF ALOE VERA GEL (Aloe Vera Linn) AND LIME PEEL EXTRACT (Citrus Aurantifolia) AS ANTIBACTERIAL IN HANDSOAP - Purwanti, Ratih; Wunga, Maria Basilia; Rizki, Cut Novrita (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2023)
The preparation of handsoap using a combination of aloe vera gel (Aloe Vera Linn) and lime peel extract (Citrus Aurantifolia) as antibacterial has been made. Aloe vera and lime peel are known to have antibacterial activity so they have the potential to be used as active substances in handsoap. The aim of this research is to determine the antibacterial activity of handsoap preparations from a combination of aloe vera gel and lime peel extract. This research uses experimental methods. Handsoap were made using 4 formulas with varying concentrations of aloe vera gel of 0% (F0), 2% (F1), 4% (F2) and 6% (F3) and a concentration of lime peel extract of 8% for all formulas. The handsoap preparation was then tested for its pH and antibacterial activity. The pH for F0 is 8.10, F1 is 6.60, F2 is 6.67 and F3 is 6.53. The results showed that the inhibition zone (mm) for F0 was 24.17, F1 was 25.97, F2 was 34.96 and F3 was 25.60. The pH of all formulas meets SNI requirements so they are safe to use, while the antibacterial activity of all formulas meets the very strong category.